Major and trace elements geochemistry of manganese nodules from WAHINE expedition in the Pacific Ocean - Stephen E Calvert; N B Price; G Ross Heath; Theodore C Moore (PANGAEA, 1978)
The bulk chemical compositions of ferromanganese nodules recovered from 14 of 38 sediment cores collected from a 230 km2 area of abyssal hill topography in the northern equatorial Pacific (8° 20 extquotesingleN, 153° 0 extquotesingleW; regional depth 5000 m) vary nonrandomly between fairly wide limits. The nodules have Mn/Fe ratios ranging from 2.60 to 5.38 and all samples contain todorokite and delta-MnO2 . The variation in the Mn/Fe ratio is governed by the total Fe contents of the nodules; Mn varies to a much smaller extent. Cu and Ni contents average about 1% and vary independently of the Mn contents. The compositional variation in the nodules is related to two features of the associated sediments, which are siliceous pelagic clays. The total Fe contents correlate positively with the oxalate-soluble Fe contents of the surface (0-2 cm) sediments; and their Mn/Fe ratios correlate negatively with the accumulation rates of the sediments. It is suspected that the composition of the nodules is influenced to a considerable extent by diagenetic reactions in the sediments, the clearest manifestation of this being the transformation of oxyhydroxide Fe into an insoluble form, possibly by the formation of smectite. This in turn leads to the formation of relatively Fe-poor ferromanganese nodules. Such nodules occur on slowly accumulating sediments where relatively more diagenetic reaction in the sediments has taken place.
Supplement to: Calvert, SE et al. (1978): Relationship between ferromanganese nodule compositions and sedimentation in a small survey area of the equatorial Pacific. Journal of Marine Research, 36, 161-183, https://store.pangaea.de/Projects/NOAA-MMS/Calvert-etal_1978.pdf